Ok al I want to know is how this boolean expression is simplified to the final answer, I can prove it to myself in a truth table, but that takes too much time.
Well, your answer is definitely good but I can't seem to follow your method. It's a pain that we can't write these things out more clearly I think. It'd be good if we could use a font where they had Not A's and NotB's etc in them.
I think the way to proceed with that problem is to use the Race Hazard Theorem. I think I'll take a look at this later on in the afternoon and see what I can come up with.
and here is the proof for that (since i cudnt digest it so i tried,my knowledge is basic and i dont remember much of digital electronics i learned myself for a brief period)
a' + ab = a'(1+b) +ab --------( 1+b)=1
= a' + a'b +ab
= a' + b(a' + a)
= a' + b(1)
= a' + b